'A Senseless, Squalid War' : Voices From Palestine, 1945-1948 - Rose, Norman (London Pimlico, 2010)
The events in Palestine between the end of the Second World War in May 1945 and the declaration of the State of Israel in May 1948 ruptured Middle Eastern history and left an indelible mark on the modern world. This book reveals the attitudes and experiences of the participants, including foot-soldiers, generals, politicians, and terrorists.
Include Index, Bibliography and Illustration
Keywords: Middle East--Palestine -- Jewish-Arab relations